SOMETHING ABOUT THE HIDDEN RESERVES OF INCREASING THE EFFICIENCY OF CLASSES DURING THE PERIOD OF MARTIAL LAW - Savenko , Oleksandr; Savenko , Tetyana; Goryunova , Maryna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article explores the forms, methods, ways and means of transforming an academic lesson into an exciting, cognitive, professionally oriented and personally meaningful process for students in the form of such activities as educational discussion, edutainment, role-playing, partner confrontation, mosaic lecture, credit lesson, brainstorming of a thematic case, virtual design of solutions to non-standard situations and deliberate provocations, educational interviews, etc. By using these formats, which do not require any financial allocations, and all depend solely on the preparedness, abilities, pedagogical talent and IQ of the teacher and the level of his communication with students, the effectiveness of the educational process, the quality of obtaining and assimilating knowledge in particular, and the quality of the education received in general, is significantly improved.